2021
DOI: 10.1522/revueot.v30n1.1294
|View full text |Cite
|
Sign up to set email alerts
|

Formation continue de la main-d’oeuvre : pour une collectivité qui se mobilise autour du développement des compétences

Abstract: La formation des travailleurs est une voie à embrasser pour conjuguer les transformations auxquelles font face les organisations québécoises. Cet article fait état des résultats d’une recherche exploratoire examinant la disposition et la capacité des PME à investir dans la formation de leurs employés, et ce, à travers les pratiques déployées et les perceptions des dirigeants de PME. Elle examine également les connaissances et les perceptions des PME à l’égard des stratégies et des programmes mis de l’avant par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Three research questions were raised: With regard to the first question, our results illustrated that overall, the SMEs portrayed in this study do not participate intensively in HRD activities, a result in line with the studies of Almeida and Aterido (2015), Johnson (2002), Nolan and Garavan (2016a) and Webster et al (2005). Our results showed HRD activities that are mostly informal and on-the-job, with learning by doing and task training as the most frequently chosen training activities, in line with the studies of Bélanger and Hart (2012), Deschênes (2021) and Sims et al (2015). HCT premises would have suggested that when HC resources are scarce, as in the context of a labor shortage, the value of developing them internally, rather than trying to acquire them externally, is expected to increase (Lepak and Snell, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Three research questions were raised: With regard to the first question, our results illustrated that overall, the SMEs portrayed in this study do not participate intensively in HRD activities, a result in line with the studies of Almeida and Aterido (2015), Johnson (2002), Nolan and Garavan (2016a) and Webster et al (2005). Our results showed HRD activities that are mostly informal and on-the-job, with learning by doing and task training as the most frequently chosen training activities, in line with the studies of Bélanger and Hart (2012), Deschênes (2021) and Sims et al (2015). HCT premises would have suggested that when HC resources are scarce, as in the context of a labor shortage, the value of developing them internally, rather than trying to acquire them externally, is expected to increase (Lepak and Snell, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…A limited number of studies have focused specifically on the types of HRD activities mobilized in SMEs in the context of labor shortages. Few recent studies showed training activities deployed in the SMEs in the province of Quebec are mostly informal, unstructured and conducted directly in the workplace (Deschênes, 2021). SMEs are investing more in mandatory training, especially those related to occupational health and safety (Bélanger and Hart, 2012).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation